A Review on various secure data access schemes and techniques in Fog for Internet of Things - Arun Kumar, Ravula; Vinuthna, Kambalapally (International Journal of Computer Sciences and Engineering, 2025)
Fog computing Provides extending feature for proper Infrastructure, Storage, Computation and services that bring cloud to the edge of network theory, fortunately or unfortunately cloud-Iot Aches from various issues such as network latency, Volume of data uploaded and the data being accessed, privacy and security. There are many schemes and methods that giving the solutions for the research being carried out in iot security, however the practical issues are still exist and in this paper the various schemes such as Distributed computing, Edge computing, homomorphic encryption, fine grained privacy preservation technique, attribute based encryption and other schemes which relates to security are reviewed and check the nature of cloud-iot based encryption schemes, In the meantime the analogy of secure access for proposed schemes such as confidentiality, availability, privacy and Integrity that securely meet the requirements of security in fog and internet of things. The Methodology is find to be metric and generic and it possess a wide range of applications and topologies with respect to networking and security. Now shall be addressing the various research techniques in order to review the security concerns in fog, cloud-IoT